Analisis Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Keputusan Pembelian Produk Kopi Neo Coffee di Kota Denpasar - Fatahillah, Mufidah Riska; Hartiati, Amna; Suhendra, Lutfi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
The purpose of this research is to determine the factors that influence consumer behavior in making decisions to purchase of kopi Neo Coffee in Denpasar City and this study aims to determine the variables that influence the decision to purchase Kopi Neo Coffee in Denpasar City. The data collection used in this research involved distributing 100 questinnaires to responden in Denpasar City, the validity and reliability test were carried out on respondents in Badung Regency. The data analysis used in this research is quantitative descriptive analysis, multiple linier regression analysis, hypothesis test (T test and F test) and coefficient of determination using SPSS Version 21. The results of the regression test show that cultural, social, personal, and psychological factors have a positive and significant influence on consumer behavior in purchasing decisions. Analysis of consumer behavior factors regarding purchasing decisions about Kopi Neo Coffee products in Denpasar City has a level of influence on purchasing decisions of 77,1%. Which means that the variable analysis of consumer behavior factor on purchasing decisions has a large enough influence.